Countdown to the year 1000 - McMullan, Kate. (New York: Scholastic, 2003)
It's the year 999, and the end of the world is coming- at least according to a mysterious prophecy. But then Wiglaf meets a strange boy who claims to come from the future. It's Zack, star of The Zach Files series by Dan Greenburg, and he says he's living proof that there is life after the year 1000!